Shaking table tests on the multi-dimensional seismic response of long-span grid structure with base-isolation. (15th December 2019) - Xu, Weizhi; Du, Dongsheng; Wang, Shuguang; Liu, Weiqing; Li, Weiwei
Highlights: Conducted multi-dimension shaking table tests of long-span isolated structure. Vertical ground motion intensified the lateral structural dynamic response. All seismic components caused significant vertical dynamic response. Base isolation technology reduced the vertical vibration of the roof. Abstract: Seismic isolation technology is being applied in large long-span-structured public buildings more and more often worldwide. Aimed to investigate the horizontal and vertical dynamic response of long-span gird structure, the shaking table tests of 1/20 scale long-span grid structures with and without base-isolation considering horizontal two-dimensional (2D) and three-dimensional (3D) seismic excitations were conducted. The test model was designed as ordinary long-span spatial grid structure, but with lead rubber bearings. Data on the acceleration, displacement, strain, and shear force of the base-isolation model and fixed-base model were collected and compared. The dynamic responses of the structure subjected to the horizontal and vertical ground motions with different intensities were studied. The experimental results showed that compared with the fixed-base model, the horizontal period and damping ratio of the base-isolation model can be significantly improved, reducing the horizontal dynamic response of the superstructure, and the horizontal isolation effect was improved with the increase of the seismic excitation intensity. The horizontal acceleration of the roof layer for the base-isolation model was amplified in 3D excitation compared to horizontal input due to horizontal-vertical coupling. Meanwhile, significant vertical acceleration and displacement responses of long-span roof for fixed-base structure were induced by horizontal seismic excitation. Although base isolation could not provide protection against vertical excitation, vertical isolation effect under 3D input could be achieved by effectively suppressing the vertical dynamic response of grid roof induced by the horizontal seismic component.